Effect of Bacterial Starter Culture Lactobacillus plantarum in Meat Fermentation of Salami on Microbiological, Chemical, and Organoleptic Properties as a Curing Agent Substitute (NaNO2) - Gharini Saraswati, Listya
In general, fermentation is a process of breaking down carbohydrates such as starch and sugar by bacteria and yeast to preserve food. Globally, the fermentation process has been used for various food products, one of which being fermented sausage. In the production of sausages, many types of meat may be used, such as poultry, beef, and swine. Meats used in the process have one similar characteristic; susceptibility to spoilage. In an attempt to avoid deterioration and spoilage, curing agents such as sodium nitrite and/ or sodium nitrate is used during fermentation. However, nutrients in meat decrease with increased amounts of preservatives and extensive processing, as there have been various research focusing on nitrite/nitrate role in the formation of carcinogenic nitrosamines. In this paper, the focus of the research is the usage of Lactobacillus plantarum, a lactic acid bacteria (LAB) as a starter culture to replace the curing agent, sodium nitrite because of its ability to increase sausage quality by inhibiting pathogenic and spoilage bacteria, as well as increasing organoleptic properties. This research aims to observe the effect of different concentrations of L. plantarum in MRS broth during sausage fermentation in comparison to the control sausage fermented naturally (no starter culture) with sodium nitrite (NaNO2) addition. The research is conducted within a span of 3 days, with four sausage groups: Sodium nitrite (100 ppm), 3% (v/w), 5% (v/w), and 7% (v/w) L. plantarum in MRS broth with a cell number of ± 105-106, fermented at 20ºC for 60 hours and cold smoked at ± 40ºC for 12 hours. Observations regarding the population dynamics of LAB is done on MRS Agar, coliform is done on EMB Agar, and total bacteria is done on Nutrient Agar. The acidification process is observed through pH testing, nutrition of the end product is measured by proximate analysis, and organoleptic properties are scored based on Hedonic testing. Population dynamics of microbes and pH testing are done every 12 hours throughout the process, whereas nutrition and organoleptic properties are measured in the end product. Results show that with increasing inoculum concentration between groups, population dynamics of LAB is stabilized. For coliform, rate of cell number growth is greater in groups with less inocolum concentration. Based on results, there is an increased duration of population dominance by LAB with increased inoculum concentration. Regarding proximate analysis, there is a significant difference in nutritional value (%) between groups. Lastly, the sausage group with the highest inoculum concentration (7% v/w) obtained the highest organoleptic scoring.